2008
DOI: 10.1523/jneurosci.2607-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Systems Controlling Speech Production

Abstract: It is proposed that the acquisition and maintenance of fluent speech depend on the rapid temporal integration of motor feedforward and polysensory (auditory and somatosensory) feedback signals. In a functional magnetic resonance imaging study on 21 healthy righthanded, English-speaking volunteers, we investigated activity within these motor and sensory pathways and their integration during speech. Four motor conditions were studied: two speech conditions (propositional and nonpropositional speech) and two sile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
87
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(105 citation statements)
references
References 49 publications
18
87
0
Order By: Relevance
“…First, our results provided evidence that RAN and reading activate similar brain regions, including areas such as the posterior MTG (semantic access; Graves et al,, 2010;Onitsuka et al, 2004;Rapcszk & Beeson, 2004;Vandenberghe, Price, Wise, Josephs, & Frackowiak, 1996;Whitney, Kirk, O'Sullivan, Ralph, & Jefferies, Cummine 22 2010), SMG (grapheme-phoneme mapping and somatosensory maps; Paulesu, Frith, & Frackowiak, 1993;Stoeckel, Gough, Watkins, & Devlin, 2009), motor and cerebellar cortex (timing and initiating motor output; He et al, 2013), SMA cortex (articulation; Alario, Chainay, Lehericy, & Cohen, 2006;Brown et al, 2009), and anterior cingulate (speech monitoring; Barch, Braver, Saab, & Noll, 2000;Chang, Kenney, Loucks, Poletto, & Ludlow, 2009;Christoffels, Formisano, & Schiller, 2007;Guenther & Vladusich, 2012;Price, 2012). Second, our results showed that RAN and reading are differentially activating regions associated with orthographic (inferior temporal gyrus; Bruno, Zumberge, Manis, Lu, & Goldman, 2008) and phonological (supramarginal gyrus, superior temporal gyrus; Dhanjal, Handunnetthi, Patel, & Wise, 2008) processing, but not articulatory/motor processing (cerebellum, supplementary motor area, precentral gyrus; Dhanjal et al, 2008), with respect to the magnitude of activation (i.e., PSC). In addition, we found direct functional neuroanatomical evidence that multiple RAN-reading neural associations exist and these associations reside predominantly within shared articulatory/motor/sequencing regions, including cerebellum, supplementary motor area and precentral gyrus.…”
Section: Discussionmentioning
confidence: 54%
“…First, our results provided evidence that RAN and reading activate similar brain regions, including areas such as the posterior MTG (semantic access; Graves et al,, 2010;Onitsuka et al, 2004;Rapcszk & Beeson, 2004;Vandenberghe, Price, Wise, Josephs, & Frackowiak, 1996;Whitney, Kirk, O'Sullivan, Ralph, & Jefferies, Cummine 22 2010), SMG (grapheme-phoneme mapping and somatosensory maps; Paulesu, Frith, & Frackowiak, 1993;Stoeckel, Gough, Watkins, & Devlin, 2009), motor and cerebellar cortex (timing and initiating motor output; He et al, 2013), SMA cortex (articulation; Alario, Chainay, Lehericy, & Cohen, 2006;Brown et al, 2009), and anterior cingulate (speech monitoring; Barch, Braver, Saab, & Noll, 2000;Chang, Kenney, Loucks, Poletto, & Ludlow, 2009;Christoffels, Formisano, & Schiller, 2007;Guenther & Vladusich, 2012;Price, 2012). Second, our results showed that RAN and reading are differentially activating regions associated with orthographic (inferior temporal gyrus; Bruno, Zumberge, Manis, Lu, & Goldman, 2008) and phonological (supramarginal gyrus, superior temporal gyrus; Dhanjal, Handunnetthi, Patel, & Wise, 2008) processing, but not articulatory/motor processing (cerebellum, supplementary motor area, precentral gyrus; Dhanjal et al, 2008), with respect to the magnitude of activation (i.e., PSC). In addition, we found direct functional neuroanatomical evidence that multiple RAN-reading neural associations exist and these associations reside predominantly within shared articulatory/motor/sequencing regions, including cerebellum, supplementary motor area and precentral gyrus.…”
Section: Discussionmentioning
confidence: 54%
“…Whereas ventral networks are implicated in pattern recognition, dorsal networks are implicated in forward-and inverse-model computation (42,44), including sensorimotor integration (42,45,48,134). This supports a role for left dorsal networks in mapping auditory representations onto the somatomotor frame of reference (135)(136)(137)(138)(139), yielding articulator-encoded speech. This ventral-dorsal dissociation is illustrated in an experiment by Buchsbaum and colleagues (2005) (110).…”
Section: And Cohen and Colleagues' (2004) Hypothesis Of An Auditory Wmentioning
confidence: 69%
“…Statistical significance of repeated measures ANOVA. speech sounds requires the analysis of rapid temporal transients that distinguish different phonemes (Lieberman, 2002) and speech production depends upon the precise temporal coordination of phonological processing regions in auditory cortex and motor speech centers in the inferior frontal lobe (Dhanjal et al, 2008). Similarly, multimodal sensory integration depends on the accurate timing of auditory and visual inputs in the posterior temporal lobe (Hein and Knight, 2008), and the analysis of visual motion in middle temporal regions requires the temporally precise analysis of visual inputs (Martinez-Trujillo et al, 2005).…”
Section: Regional Variations In Fa and Mtrmentioning
confidence: 99%